Breathable waterproof flame-retardant mattress foam and preparation method thereof

By preparing mattress foam containing vinyl silicone oil, white carbon black, palm staple fiber and other materials, the problems of polyurethane foam are flammable, easy to absorb and deform, and the improvement of breathable, waterproof, flame retardant and mechanical strength is achieved, extending service life and improving sleep comfort and safety.

CN119529541APending Publication Date: 2025-02-28GUILIN XIANGZE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771622.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Polyurethane foam is flammable, easy to absorb moisture and mold, affecting sleep quality and safety. At the same time, it is easy to deform or damage after being subjected to pressure for a long time, affecting its service life.

Method used

Component A is prepared by using vinyl silicone oil, white carbon black, palm staple fiber, zinc oxide whiskers, aluminum-based flame retardant powder and platinum catalysts, and component B is prepared by combining vinyl silicone oil, white carbon black, foaming agent and cyclohexanol inhibitor. Component B is prepared by vacuum stirring, oven pre-foaming and secondary foaming curing, forming a mattress foam with breathable, waterproof, flame retardant and mechanical strength.

Benefits of technology

The breathable, waterproof and flame retardant properties of mattress foam are achieved, while improving mechanical strength, avoiding deformation and damage, extending service life, and improving sleep comfort and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170411120000061
    Figure BDA0005170411120000061
  • Figure BDA0005170411120000071
    Figure BDA0005170411120000071
  • Figure BDA0005170411120000072
    Figure BDA0005170411120000072
Patent Text Reader

Abstract

The invention relates to the technical field of mattress manufacturing and processing, in particular to breathable waterproof flame-retardant mattress foam and a preparation method thereof. The flame-retardant silicone rubber is prepared from a component A and a component B. The component A is prepared from, by weight, 100 parts of vinyl silicone oil, 20-30 parts of white carbon black, 30-50 parts of palm short fibers, 5-10 parts of zinc oxide whiskers, 10-15 parts of aluminum flame-retardant powder and 1-2 parts of a platinum catalyst. The component B is prepared from the following raw materials in parts by weight: 100 parts of vinyl silicone oil, 30-40 parts of white carbon black, 3-5 parts of a foaming agent and 0.5-1 part of a cyclohexanol inhibitor, and the breathable waterproof flame-retardant mattress foam prepared by the formula has good breathability, waterproofness, flame retardance and mechanical strength, and is not easy to deform or damage in a long-time use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of mattress manufacturing and processing, and more specifically, to a breathable, waterproof and flame-retardant mattress foam and a preparation method thereof. Background Art

[0002] Foam has good support, shock absorption and comfort, and can bring people a good sleeping experience. It is a material commonly used in the manufacture of mattresses. Currently, polyurethane foam is commonly used because it has excellent resilience and can be adaptively adjusted according to the weight and shape of the human body to provide fitting support, thereby enhancing the comfort of the mattress. At the same time, polyurethane foam has a relatively dense pore structure inside, which can keep the mattress dry, avoid moisture and stuffiness, and help improve sleep quality.

[0003] However, polyurethane is a flammable material, and it is difficult to effectively contain the rapid spread of fire in the event of a fire, which undoubtedly increases the potential safety risks. At the same time, it is precisely because the foam material contains a large number of pores that easily absorb moisture from the surrounding environment, and it is easy to mold in a humid environment.

[0004] Since silicone rubber itself has high thermal stability, it can maintain the stability of its physical and chemical properties at high temperatures. At the same time, the surface energy of silicone rubber is smaller than that of most organic materials, and it has low hygroscopicity. The water absorption rate of long-term immersion in water is only about 1%, which makes it difficult for mold to grow and reproduce on the surface of silicone rubber. Therefore, people use silicone rubber foaming materials instead of polyurethane foam materials to solve the problem of polyurethane foam being flammable and easy to absorb moisture and mold. However, the main chain of silicone rubber is composed of alternating silicon atoms and oxygen atoms. This special molecular structure makes silicone rubber easy to deform when subjected to force. In addition, silicone rubber usually has organic groups on its side chains. The interaction between these groups is weak, which further affects the mechanical strength of the material. The mattress will be deformed or damaged when subjected to high pressure for a long time, thus affecting its service life and comfort. Summary of the invention

[0005] In order to provide a mattress foam that is waterproof, breathable, flame-retardant, durable and not easy to deform, the present application provides a breathable, waterproof and flame-retardant mattress foam and a preparation method thereof.

[0006] In a first aspect, the present application provides a breathable, waterproof and flame-retardant mattress foam, which adopts the following technical solution: A breathable, waterproof and flame-retardant mattress foam is prepared from component A and component B, wherein component A is prepared from the following raw materials in the following weight percentages: 100 parts of vinyl silicone oil 20-30 parts of white carbon black Palm staple fiber 30-50 parts Zinc oxide whisker 5-10 parts Aluminum flame retardant powder 10-15 parts 1-2 parts of platinum catalyst Component B is prepared from the following raw materials in weight percentage: 100 parts of vinyl silicone oil 30-40 parts of white carbon black 3-5 parts of foaming agent Cyclohexanol inhibitor 0.5-1 part.

[0007] By adopting the above technical solution, the air-permeable, waterproof and flame-retardant mattress foam is obtained, which has good air permeability, waterproofness, flame retardancy and mechanical strength, and is not easy to deform or damage during long-term use.

[0008] In this application, the flame retardant properties of the foam are improved by adding aluminum flame retardant powder, which can effectively curb the rapid spread of fire in the event of a fire and reduce safety risks. The combination of raw materials such as vinyl silicone oil and white carbon black makes the foam have low hygroscopicity, can keep dry for a long time, avoid moisture and stuffiness, and prevent the growth and reproduction of mold. The addition of palm staple fibers and zinc oxide whiskers enhances the mechanical strength of the foam. The reason is that palm staple fibers and zinc oxide whiskers can be evenly dispersed in the foam to form a network structure, improve the mechanical properties of the foam such as tensile strength and compression resistance, make it difficult to deform or damage when subjected to high pressure for a long time, and extend the service life. The foaming agent decomposes and produces gas during the heating process, so that a uniform pore structure is formed inside the foam. At the same time, the addition of palm staple fibers and zinc oxide whiskers also provides good air permeability for the mattress, helps to maintain air circulation inside the mattress, avoids moisture and stuffiness, and increases the softness and comfort of the mattress.

[0009] The cyclohexanol inhibitor is used to adjust the foaming process to make the pores of moderate size, which not only ensures air permeability but also avoids the loose structure caused by excessive expansion. The synergistic effect of the foaming agent and the cyclohexanol inhibitor forms a uniform pore structure inside the foam, making the pore structure more uniform and dense, thereby improving the support and stability of the mattress.

[0010] Preferably, the palm staple fiber is prepared by the following method: A: Collect the palm leaves, remove the woody parts, and obtain pure palm leaves; B: Place the pure palm leaves in an environment at a temperature of 40-50°C and air dry for 8-10 days, spray water once every 12 hours, and do not spray water in the last two days to obtain processed palm leaves; C: crushing the processed palm leaves to a length of 1-10 microns to obtain crushed palm leaves; D: Mix the silane coupling agent with ethanol, then mix with the crushed palm leaves, stir for 1-2 hours, remove the ethanol, and obtain silanized palm leaf powder; E: Dissolve the polyurethane in an organic solvent, add the silanized palm leaf powder and stir, then perform wet spinning to obtain fibers, and grind the fibers to obtain palm staple fibers.

[0011] By adopting the above technical solution, the toughness of the palm short fiber is improved, and when used to prepare mattress foam, the toughness of the mattress foam can be enhanced, so that it can better maintain the integrity of shape and structure when subjected to external forces, and is not easy to break or damage. At the same time, the unique structure of the fiber in the palm leaf is also used to increase air circulation, so that the inside of the mattress can remain dry and avoid moisture and stuffiness, thereby improving sleep comfort.

[0012] The fibers in palm leaves have good air permeability and strength. They are used to prepare foams, which can improve the mechanical strength and air permeability of foams. However, they need urgent treatment to achieve better results. The woody part of palm leaves is hard in texture, which is not conducive to subsequent processing and the softness of the fibers, so it is removed in step A. Drying palm leaves at a suitable temperature can maintain the integrity of their fiber structure, increase the toughness of the fibers in the palm leaves, and remove excess water to provide conditions for subsequent crushing. Spraying water is to maintain the humidity of the palm leaves, prevent them from becoming brittle due to excessive drying, and ensure the toughness of the fibers in the palm leaves. Stopping spraying water in the last two days is to ensure that the palm leaves are completely dry. Crushing palm leaves into fine lengths can better combine them with silane coupling agents and polyurethanes to form a uniform fiber structure. Silane coupling agents can improve the compatibility between palm leaf fibers and polymer materials such as polyurethanes, enhance the bonding force between them, and thus improve the durability and stability of foams. Ethanol, as a solvent, helps the silane coupling agent to be evenly distributed on the palm leaf fibers. After removing the ethanol, the silane coupling agent is firmly attached to the fiber surface.

[0013] Polyurethane has good elasticity and toughness. Dissolving it in an organic solvent and mixing it with silanized palm leaf powder for wet spinning can produce fibers with excellent performance. It not only has the natural characteristics of palm leaf fibers, but also has the elasticity and toughness of polyurethane. The fibers obtained by spinning are crushed to obtain palm short fibers. These short fibers can be evenly dispersed in the mattress foam material to form a microporous structure, which improves the air permeability and comfort of the mattress. At the same time, due to the enhanced bonding between palm short fibers and other raw materials of the foam, the durability and stability of the foam are also improved.

[0014] Preferably, the weight ratio of the crushed palm leaves, the silane coupling agent and the polyurethane is 5:1:(10-12).

[0015] By adopting the above technical solution, the dosage of crushed palm leaves, silane coupling agent and polyurethane is optimized, so that the bonding strength between crushed palm leaves and polyurethane is better, and the formed foam has support, elasticity and durability, so that the mattress can adapt to the weight and shape of the human body and can be used for a long time.

[0016] Preferably, the usage ratio of the polyurethane to the organic solvent is 0.1 g / 1-1.5 ml.

[0017] By adopting the above technical solution, the ratio of polyurethane and organic solvent is optimized, so that polyurethane can be fully dissolved in the organic solvent to form a uniform solution, which helps to make polyurethane fibers be formed evenly and continuously in the subsequent wet spinning process, thereby improving the uniformity and stability of the mattress foam material.

[0018] Preferably, the foaming agent is composed of aliphatic hydrocarbon and azo compound in a weight ratio of 1:(2-3).

[0019] By adopting the above technical solution and optimizing the type and amount of foaming agent, aliphatic hydrocarbons and azo compounds have a synergistic effect in the foaming process. Aliphatic hydrocarbons can provide stable foaming performance, while azo compounds can quickly decompose to produce gas to drive the foaming process. When the ratio of these two components is moderate, their synergistic effect can be fully exerted, the foaming effect is improved, and it helps to form a uniform foaming structure, and improve the overall comfort, support and breathability of the foam.

[0020] Preferably, the vinyl silicone oil is composed of vinyl silicone oil with a vinyl content of 0.05-0.5% and vinyl silicone oil with a vinyl content of 1-3%.

[0021] By adopting the above technical solutions, the amount and type of vinyl silicone oil are optimized, and the elasticity, strength and softness of the foam are further improved, which helps to extend the service life of the mattress and reduce the performance degradation caused by wear. Vinyl silicone oils with different vinyl contents play a synergistic role in mattress foam materials. Silicone oils with low vinyl content mainly provide lubricity and softness, while silicone oils with high vinyl content mainly enhance wear resistance and chemical stability, allowing the foam to maintain long-lasting performance and quality stability during use.

[0022] Preferably, the aluminum-based flame retardant powder is composed of aluminum hydroxide and aluminum hypophosphite powder in a weight ratio of 5:(1-2).

[0023] By adopting the above technical solution, the amount and type of aluminum flame retardant powder are optimized, and the flame retardant performance of the foam is further improved. Among them, after the aluminum hydroxide decomposes, an aluminum oxide protective film is formed on the surface of the combustible material, isolating oxygen and preventing the combustion from continuing. After the aluminum hypophosphite decomposes, it will also form a non-combustible solid in the condensed phase, covering the surface of the combustible material, enhancing the oxygen isolation effect. The combination of the two makes the flame retardant effect of the foam better.

[0024] Preferably, the usage ratio of the component A to the component B is 1:(1-1.5).

[0025] By adopting the above technical solution and optimizing the dosage of component A and component B, it can be ensured that component A and component B can fully contact each other during the reaction process, and the structure formed by the reaction is more stable, which helps to improve the overall strength of the foam.

[0026] Preferably, the platinum content of the platinum catalyst is 3000-5000 ppm.

[0027] By adopting the above technical solution, the platinum catalyst is optimized to promote the reaction of component A and component B, improve the reaction efficiency, and form a foam with stable structure, good elasticity, good support, good softness and long durability. In a second aspect, the present application provides a method for preparing a breathable, waterproof and flame-retardant mattress foam, using the following technical solution: A method for preparing a breathable, waterproof and flame-retardant mattress foam comprises the following preparation steps: S1. Vinyl silicone oil, white carbon black, aluminum flame retardant powder, palm staple fiber, zinc oxide whisker and platinum catalyst are fully mixed, and then stirred for 30-50 minutes under vacuum conditions until the components are thoroughly dispersed and air bubbles in the mixture are removed to obtain component A; S2, fully mixing vinyl silicone oil, white carbon black, blowing agent and cyclohexanol inhibitor, and then stirring for 30-50 minutes under vacuum conditions until the components are thoroughly dispersed and air bubbles in the mixture are removed to obtain component B; S3, mixing component A and component B, maintaining the temperature at 13-15° C. to obtain a mixture; S4, applying the mixture on the release film, maintaining the temperature at 15-17°C during the operation, and then putting it into an oven preset at 70-90°C for pre-foaming for 30-40 minutes to obtain pre-foamed foam cotton; S5. Place the pre-expanded foam cotton in an oven at a temperature of 130-180°C for secondary foaming and curing for 3-4 hours to obtain a finished product.

[0028] In steps S1 and S2, stirring under vacuum conditions ensures that all raw materials are thoroughly dispersed and mixed evenly, avoiding local concentrations that are too high or too low, which provides a good foundation for subsequent chemical reactions and the formation of foam structures. In step S3, the temperature of component A and component B when mixing is maintained at 13-15°C, which helps slow down the reaction rate and make the mixing more uniform. In steps S4 and S5, the preset oven temperature ensures that the pre-foaming and secondary foaming curing processes of the foam can be carried out within the optimal temperature range, thereby obtaining a foam structure with high strength and stable structure.

[0029] In summary, this application has the following beneficial effects: 1. Component A is prepared by combining vinyl silicone oil, white carbon black, palm short fiber, zinc oxide whisker, aluminum flame retardant powder and platinum catalyst, component B is prepared by combining vinyl silicone oil, white carbon black, foaming agent and hexanol inhibitor, and then components A and B are mixed to prepare foam, so that the foam has air permeability, waterproof, flame retardant properties and good mechanical strength, is not easily deformed or damaged during use, and the service life of the mattress is extended. DETAILED DESCRIPTION Example

[0030] The vinyl silicone oil was purchased from Hubei Longsheng Sihai New Materials Co., Ltd. and is SH series vinyl silicone oil.

[0031] The palm staple fiber was purchased from Qingdao Port Land Transport International Logistics Co., Ltd. and crushed into 1-2 microns.

[0032] Polyurethane was purchased from Dongguan Yili Plastic Co., Ltd. The brand is BASF of Germany and the model is B95A5000.

[0033] Example 1 A breathable, waterproof and flame-retardant mattress foam is prepared by the following method: S1. 1000 g of vinyl silicone oil, 200 g of white carbon black, 100 g of aluminum flame retardant powder (aluminum hydroxide), 300 g of palm staple fiber, 50 g of zinc oxide whisker and 10 g of platinum catalyst (Castell platinum catalyst) were fully mixed, and then stirred for 30 minutes under vacuum until the ingredients were thoroughly dispersed and air bubbles in the mixture were removed to obtain component A; S2, 1000 g of vinyl silicone oil, 300 g of white carbon black, 30 g of blowing agent (n-pentane) and 5 g of cyclohexanol inhibitor (1-ethynylcyclohexanol) were fully mixed, and then stirred for 30 minutes under vacuum until the components were thoroughly dispersed and air bubbles in the mixture were removed to obtain component B; S3. Use a fully automatic feeder to pump component A and component B separately, set the feed pressure to 0.2MPa, ensure that a low pressure state is maintained during the mixing process to reduce gas entrainment; stir and mix components A and B at a speed of 800rpm, and use cold water circulation to cool to a stable temperature of about 13°C. The dosage ratio of component A to component B is 1:1; S4, applying the mixture on the release film, keeping the temperature at 15°C during the operation, and then putting it into an oven preset at 70°C for pre-foaming for 30 minutes to obtain pre-foamed foam cotton; S5. Place the pre-expanded foam cotton in an oven at 130° C. again for secondary foaming and curing for 3 hours to obtain a breathable, waterproof and flame-retardant mattress foam cotton.

[0034] The vinyl content in vinyl silicone oil is 1%.

[0035] The platinum content in the platinum catalyst is The difference between Example 2-3 and Example 1 is that the types of raw materials, amounts and experimental parameters for preparing the breathable, waterproof and flame-retardant mattress foam are different. The specific differences are shown in Table 1: Table 1: Types of raw materials, dosages and experimental parameters for preparing breathable, waterproof and flame-retardant mattress foams in Examples 1-3 1000ppm.

[0036] In Example 2, the usage ratio of component A to component B is 1:1.2.

[0037] In Example 3, the usage ratio of component A to component B is 1:1.5.

[0038] Example 4 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that the palm short fiber is prepared by the following method: A: Collect 1500g of palm leaves, remove the woody parts, and obtain pure palm leaves; B: Place the pure palm leaves in an environment at a temperature of 40°C and dry them for 8 days, spraying them with water every 12 hours, with the amount of water sprayed being 15g of the palm leaves. No water spraying is required for the last two days, thus obtaining the processed palm leaves; C: crushing the processed palm leaves to a length of 1-2 microns to obtain crushed palm leaves; D: 100 g of silane coupling agent (γ-aminopropyltriethoxysilane) was mixed with 600 g of ethanol, and then the crushed palm leaves were mixed, stirred for 1 hour, and the ethanol was removed to obtain silanized palm leaf powder; E: 1000 g of polyurethane was dissolved in 10000 g of organic solvent (dimethylformamide), and then silanized palm leaf powder was added and stirred, and then wet spinning was performed to obtain fibers, and the fibers were crushed to obtain palm short fibers.

[0039] The difference between Example 5-6 and Example 4 is that the raw material types, amounts and experimental parameters for preparing palm staple fibers are different. The specific differences are shown in Table 2: Table 2 Raw material types, amounts and experimental parameters for preparing palm staple fibers in Examples 4-6 Example 7 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that in step B, water does not need to be sprayed every 12 hours.

[0040] Example 8 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that polyurethane is replaced by polylactic acid.

[0041] Polylactic acid was purchased from Hubei Kewode Chemical Co., Ltd. with model number 26100-51-6.

[0042] Example 9 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that no silane coupling agent is added in step D.

[0043] Example 10 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that the foaming agent is composed of aliphatic hydrocarbon (n-pentane) and azo compound (azobisisobutylcyanide) in a weight ratio of 1:2.

[0044] Embodiment 11 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 4 is that the foaming agent is composed of aliphatic hydrocarbon (n-pentane) and azo compound (azobisisobutylcyanide) in a weight ratio of 1:2.

[0045] Example 12 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that the vinyl silicone oil is composed of vinyl silicone oil with a vinyl content of 0.05% and vinyl silicone oil with a vinyl content of 1%.

[0046] Embodiment 13 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 4 is that the vinyl silicone oil is composed of vinyl silicone oil with a vinyl content of 0.5% and vinyl silicone oil with a vinyl content of 3%.

[0047] Embodiment 14 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 10 is that the vinyl silicone oil is composed of vinyl silicone oil with a vinyl content of 0.5% and vinyl silicone oil with a vinyl content of 3%.

[0048] Embodiment 15 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 1 is that the aluminum flame-retardant powder is composed of aluminum hydroxide and aluminum hypophosphite powder in a weight ratio of 5:1.

[0049] Example 16 A breathable, waterproof and flame-retardant mattress foam. The difference between this embodiment and embodiment 4 is that the aluminum flame-retardant powder is composed of aluminum hydroxide and aluminum hypophosphite powder in a weight ratio of 5:2.

[0050] Comparative Example Comparative Example 1 A breathable, waterproof and flame-retardant mattress foam. The difference between this comparative example and Example 1 is that 10% glass fiber PC is used instead of palm staple fiber.

[0051] 10% glass fiber PC was purchased from Shanghai Longjiuhui Import and Export Co., Ltd., model number EXL1810T-7R1D047.

[0052] Comparative Example 2 A breathable, waterproof and flame-retardant mattress foam. The difference between this comparative example and Example 1 is that chitosan is used instead of zinc oxide whiskers.

[0053] Comparative Example 3 A breathable, waterproof and flame-retardant mattress foam. The difference between this comparative example and Example 1 is that in step S3, cold water is circulated and cooled until the temperature is stabilized at 25°C.

[0054] Comparative Example 4 A breathable, waterproof and flame-retardant mattress foam. The difference between this comparative example and Example 1 is that in step S4, the mixture is applied to a release film, and the temperature is maintained at 25° C. during the operation.

[0055] Comparative Example 5 A breathable, waterproof and flame-retardant mattress foam. The difference between this comparative example and Example 1 is that in step S4, the foam is sent to an oven preset at 130° C. for pre-foaming for 30 minutes to obtain pre-foamed foam.

[0056] Detection method / test method Air permeability: Tested in accordance with GB / T 10655-2003.

[0057] Water absorption test: refer to Section 6.2.3 of national standard GB / T18944.1-2003 for testing. The size of the foam test sample is 50mm (length) × 50mm (width) × 15mm (thickness). The test pressure is 20kPa. Soak in distilled water for 3min → release the pressure and soak in distilled water for 3min. The laboratory environment temperature is 25℃ and the humidity is 50%. The water absorption vacuum device model CXK-A is used for testing.

[0058] Tensile strength test: GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" is used for testing.

[0059] Compression set rate: in accordance with GB / T 6669-2008.

[0060] Hardness: Refer to ASTM D 2240 standard to test the hardness of the product.

[0061] Flame retardancy: Refer to GB / T10707-2008 "Determination of Rubber Combustion Performance". The experimental data are shown in Table 3: Table 3 Experimental data of Examples 1-16 and Comparative Examples 1-5 By comparing Example 1 with Comparative Examples 1-5, the air permeability values, tensile strength values ​​(except Example 1) and hardness values ​​in Comparative Examples 1-5 are all smaller than those in Example 1; the water absorption values ​​and compression permanent deformation rates of Comparative Examples 1-5 are all greater than those in Example 1, indicating that by using palm staple fibers and zinc oxide whiskers together with vinyl silicone oil, white carbon black and other raw materials in the present application, combined with the process technology in the present application, the air permeability, waterproofness, tensile strength and hardness of the foam can be greatly improved, while its compression permanent deformation rate can be greatly reduced.

[0062] Comparing Example 1 with Examples 4-6, the values ​​of air permeability, tensile strength, and hardness in Example 4-8 are all greater than those in Example 1; the values ​​of water absorption and compression permanent deformation in Example 4-6 are all less than those in Example 1; Comparing Example 4 with Examples 7-9, the values ​​of air permeability, tensile strength, and hardness in Examples 7-9 are all lower than those in Example 4; the values ​​of water absorption and compression permanent deformation in Examples 7-9 are all higher than those in Example 4; It can be seen from Examples 1, 4-6 and Examples 4, 7-9 that the palm staple fibers prepared by the process of the present application are used to prepare foam, which can improve the air permeability, waterproofness, tensile strength and hardness of the foam, while reducing its compression permanent deformation rate.

[0063] Comparing Example 1 with Example 10, the air permeability value, tensile strength value, and hardness value of Example 10 are all greater than those of Example 1; the water absorption value and compression permanent deformation rate of Example 10 are both less than those of Example 1; Comparing Example 4 with Example 11, the air permeability value, tensile strength value and hardness value of Example 11 are all smaller than those of Example 4; the water absorption value and compression permanent deformation rate of Example 11 are both larger than those of Example 4; It can be seen from Examples 1, 10 and Examples 4, 11 that optimizing the type and amount of the foaming agent is beneficial to improving the air permeability, waterproofness, tensile strength and hardness of the foam, while reducing its compression permanent deformation rate.

[0064] Comparing Example 1 with Example 12, the air permeability value, tensile strength value, and hardness value of Example 12 are all greater than those of Example 1; the water absorption value and compression permanent deformation rate of Example 12 are both less than those of Example 1; Comparing Example 4 with Example 13, the air permeability value, tensile strength value, and hardness value of Example 13 are all smaller than those of Example 4; the water absorption value and compression permanent deformation rate of Example 13 are both larger than those of Example 4; Comparing Example 10 with Example 14, the air permeability value, tensile strength value and hardness value of Example 14 are all smaller than those of Example 10; the water absorption value and compression permanent deformation rate of Example 14 are both larger than those of Example 10; It can be seen from Examples 1, 12, 4, 13, 10, and 14 that the use of vinyl silicone oil with a low vinyl content and vinyl silicone oil with a high vinyl content together is beneficial to improving the air permeability, waterproofness, tensile strength, and hardness of the foam while reducing its compression set rate.

[0065] Comparing Example 1 with Example 15, the air permeability value, tensile strength value, and hardness value of Example 15 are all greater than those of Example 1; the water absorption value and compression permanent deformation rate of Example 15 are both less than those of Example 1; Comparing Example 4 with Example 16, the air permeability value, tensile strength value, and hardness value of Example 16 are all smaller than those of Example 4; the water absorption value and compression permanent deformation rate of Example 61 are both larger than those of Example 4; It can be seen from Examples 1, 15 and Examples 4, 16 that optimizing the amount and type of aluminum flame retardant powder is beneficial to improving the air permeability, waterproofness, tensile strength and hardness of the foam, while reducing its compression permanent deformation rate.

[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A breathable, waterproof and flame-retardant mattress foam, characterized in that: It is prepared from component A and component B, wherein component A is prepared from the following raw materials in weight percentage: 100 parts of vinyl silicone oil 20-30 parts of white carbon black Palm staple fiber 30-50 parts Zinc oxide whisker 5-10 parts Aluminum flame retardant powder 10-15 parts 1-2 parts of platinum catalyst Component B is prepared from the following raw materials in weight percentage: 100 parts of vinyl silicone oil 30-40 parts of white carbon black 3-5 parts of foaming agent Cyclohexanol inhibitor 0.5-1 part.

2. The breathable, waterproof and flame-retardant mattress foam according to claim 1, characterized in that: The palm staple fiber is prepared by the following method: A: Collect the palm leaves, remove the woody parts, and obtain pure palm leaves; B: Place the pure palm leaves in an environment at a temperature of 40-50°C and air dry for 8-10 days, spray water once every 12 hours, and do not spray water in the last two days to obtain processed palm leaves; C: crushing the processed palm leaves to a length of 1-10 microns to obtain crushed palm leaves; D: Mix the silane coupling agent with ethanol, then mix with the crushed palm leaves, stir for 1-2 hours, remove the ethanol, and obtain silanized palm leaf powder; E: Dissolve the polyurethane in an organic solvent, add the silanized palm leaf powder and stir, then perform wet spinning to obtain fibers, and grind the fibers to obtain palm staple fibers.

3. The breathable, waterproof and flame-retardant mattress foam according to claim 2, characterized in that: The weight ratio of the crushed palm leaves, the silane coupling agent and the polyurethane is 5:1:(10-12).

4. The breathable, waterproof and flame-retardant mattress foam according to claim 1, characterized in that: The usage ratio of the polyurethane to the organic solvent is 0.1 g / 1-1.5 ml.

5. The breathable, waterproof and flame-retardant mattress foam according to claim 4, characterized in that: The foaming agent is composed of aliphatic hydrocarbon and azo compound in a weight ratio of 1:(2-3).

6. The breathable, waterproof and flame-retardant mattress foam according to claim 4, characterized in that: The vinyl silicone oil is composed of vinyl silicone oil with a vinyl content of 0.05-0.5% and vinyl silicone oil with a vinyl content of 1-3%.

7. The breathable, waterproof and flame-retardant mattress foam according to claim 1, characterized in that: The aluminum flame retardant powder is composed of aluminum hydroxide and aluminum hypophosphite powder in a weight ratio of 5: (1-2).

8. The breathable, waterproof and flame-retardant mattress foam according to claim 1, characterized in that: The dosage ratio of the component A to the component B is 1:(1-1.5).

9. The breathable, waterproof and flame-retardant mattress foam according to claim 1, characterized in that: The platinum content of the platinum catalyst is 3000-5000ppm.

10. A method for preparing the breathable, waterproof and flame-retardant mattress foam according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1. Vinyl silicone oil, white carbon black, aluminum flame retardant powder, palm staple fiber, zinc oxide whisker and platinum catalyst are fully mixed, and then stirred for 30-50 minutes under vacuum conditions until the components are thoroughly dispersed and air bubbles in the mixture are removed to obtain component A; S2, fully mixing vinyl silicone oil, white carbon black, blowing agent and cyclohexanol inhibitor, and then stirring for 30-50 minutes under vacuum conditions until the components are thoroughly dispersed and air bubbles in the mixture are removed to obtain component B; S3, mixing component A and component B, maintaining the temperature at 13-15° C. to obtain a mixture; S4, applying the mixture on the release film, maintaining the temperature at 15-17°C during the operation, and then putting it into an oven preset at 70-90°C for pre-foaming for 30-40 minutes to obtain pre-foamed foam cotton; S5. Place the pre-expanded foam cotton in an oven at a temperature of 130-180°C for secondary foaming and curing for 3-4 hours to obtain a finished product.